PERUBAHAN LINGKUNGAN DAN KARAKTER SISTEM PENGENDAPAN PLISTOSEN AKHIR HOLOSEN DI DATARAN PANTAI PEKALONGAN, JAWA TENGAH - Herman Moechtar; Herman mulyana; Suyatman Hidayat (Pusat Survei Geologi, 2009)
The study of the environmental changes and character of the depositonal systems during Late Plistocene to Holocene on the Pekalongan coastalplain was based on analyses of the sedimentology and stratigraphy of fourteen boreholes. The penentration of the bore head varied from 7.70 to 15.80 m. Six depositional environments which occurred above the Damar Formation (QTd) are: linier clastic deposits (offshore, nearshore, and beach), fluvial deposits (river channel and floodplain), and swamp deposits. These deposits are separated by three depositional intervals (IP I-III). Based on the correlation of lateral and vertical stratigraphic successions, the environmental changes and character of the depostional systems are controled by sea level changes during the Late Pleistocene which were related by glacial and inter-glacial periods. Probably, after deposition of IP I, a local tectonichsve controled deplifting of the are. Keywords: Sedimentology, Stratigraphy, late Pleistocene - Holocene